2006
DOI: 10.5144/0256-4947.2006.116
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal atresia with or without tracheoesophageal fistula: success and failure in 94 cases

Abstract: BACKGROUNDThe management of newborns with esophageal atresia (EA) with or without tracheoesophageal fistula (TEF) has evolved considerably over the years. Currently an overall survival of 85% to 90% has been reported from developed countries. In developing countries, several factors contribute to higher mortality rates. We describe our experience with 94 consecutive cases of EA with or without TEF.PATIENTS AND METHODSWe retrospectively studied 94 patients with EA with or without TEF treated at our hospital ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 15 publications
1
17
1
7
Order By: Relevance
“…This is due to the fact that we also included studies with very-lowbirth-weight infants and articles from third world countries in this report. 27,[31][32][33][34] However, it has been suggested that birth weight is nowadays not an important factor as it was previously, although major cardiac anomalies are still of poor prognostic aspect. 35 In our report, leakage rate remained stable over time between 11 and 16%, suggesting that surgical variations do not have any substantial influence on this complication.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the fact that we also included studies with very-lowbirth-weight infants and articles from third world countries in this report. 27,[31][32][33][34] However, it has been suggested that birth weight is nowadays not an important factor as it was previously, although major cardiac anomalies are still of poor prognostic aspect. 35 In our report, leakage rate remained stable over time between 11 and 16%, suggesting that surgical variations do not have any substantial influence on this complication.…”
Section: Discussionmentioning
confidence: 99%
“…Leur admission médiane de 3 [1–9] jours après la naissance, était directe. La mortalité globale était de 76,5%.…”
Section: Résultatsunclassified
“…The common associated anomalies in non-syndromic oesophageal atresia include the cardiovascular system (CVS), genitourinary tract (GUT), gastrointestinal tract (GIT), musculoskeletal system (MSS), and central nervous system (CNS) ( Table 4). Cardiovascular anomalies tend to occur most frequently (Table 4) [23,25,27]. This is followed by the GUT, GIT, MSS, and CNS (neurologic anomalies).…”
Section: Associated Anomaliesmentioning
confidence: 99%
“…Disconnection of distal TOF is done at most centres through thoracotomy. At our centre, however, this is done by dividing the abdominal oesophagus during the placement of the feeding gastrostomy [27]. This helps to avoid the stress of thoracotomy that may negatively affect patient outcome.…”
Section: Operative Management Of Oesophageal Atresiamentioning
confidence: 99%